Peran Pekerja Migran Perempuan dan Kontribusinya Terhadap Kesejahteraan Ekonomi Rumah Tangga: Relevansi dengan Hukum Islam - Janwari, Yadi; Akmaliyah, Akmaliyah; Sumiati, Sumiati; Fitriani, Putri Diesy; Sari, Rosi Hasna (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2024)
The study examines the phenomenon of a significant increase in female migrant workers in Karawang Regency, an area with the highest Regency/City Minimum Wage (MSW) in West Java. The research aims to identify the factors that drive women in Karawang to become migrant workers and analyze the impact of such migration on family welfare from the perspective of Islamic law. Using a qualitative approach, the study found that several factors, such as education level, family economic condition, social status, job competitiveness, and divorce rate, play a significant role in encouraging women to become migrant workers. The results show that women's migration has multiple positive and negative impacts on family welfare. In the context of Islamic law, the research concludes that the activities of female migrant workers are permissible.